Gut microbiota-derived metabolites confer protection against SARS-CoV-2 infection. (31st December 2022) - Brown, Julia A.; Sanidad, Katherine Z.; Lucotti, Serena; Lieber, Carolin M.; Cox, Robert M.; Ananthanarayanan, Aparna; Basu, Srijani; Chen, Justin; Shan, Mengrou; Amir, Mohammed; Schmidt, Fabian; Weisblum, Yiska; et al.
ABSTRACT: The gut microbiome is intricately coupled with immune regulation and metabolism, but its role in Coronavirus Disease 2019 (COVID-19) is not fully understood. Severe and fatal COVID-19 is characterized by poor anti-viral immunity and hypercoagulation, particularly in males. Here, we define multiple pathways by which the gut microbiome protects mammalian hosts from SARS-CoV-2 intranasal infection, both locally and systemically, via production of short-chain fatty acids (SCFAs). SCFAs reduced viral burdens in the airways and intestines by downregulating the SARS-CoV-2 entry receptor, angiotensin-converting enzyme 2 (ACE2), and enhancing adaptive immunity via GPR41 and 43 in male animals. We further identify a novel role for the gut microbiome in regulating systemic coagulation response by limiting megakaryocyte proliferation and platelet turnover via the Sh2b3-Mpl axis. Taken together, our findings have unraveled novel functions of SCFAs and fiber-fermenting gut bacteria to dampen viral entry and hypercoagulation and promote adaptive antiviral immunity.